2020
DOI: 10.1186/s12885-020-07559-w
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of vitamin D receptor in breast cancer: a systematic review and meta-analysis

Abstract: Background A higher vitamin D intake improves the prognosis of early stage breast cancer (BC) patients. We hypothesized that vitamin D intake should refer to vitamin D receptor (VDR) expression. In order to prove this hypothesis, we first intend to evaluate the correlation between VDR expression and prognosis of BC patients using meta-analysis. Methods Literatures from PubMed, Embase, and the Cochrane Library (last update by May 20, 2020) were retrieved to find studies assessing the prognostic role of VDR in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 38 publications
(42 reference statements)
2
24
0
Order By: Relevance
“…Interestingly, women with breast cancer with 25(OH)D level ≥ 99 nmol/L also had worse PFS and OS [ 237 ]. Of note, Xu et al showed that the level of VDR protein expression in neoplastic cells in patients with breast cancer was related to OS, therefore, they recommned individualized vitamin D intake to assess breast cancer prognosis [ 238 ]. In case of lung cancer, Huang et al conducted a meta-analysis of eight cohort studies to evaluate the correlation between serum 25(OH)D level and OS.…”
Section: What Do We Know So Far About Vitamin D In Cancer Prevention and Prognosis From Clinical Trials?mentioning
confidence: 99%
“…Interestingly, women with breast cancer with 25(OH)D level ≥ 99 nmol/L also had worse PFS and OS [ 237 ]. Of note, Xu et al showed that the level of VDR protein expression in neoplastic cells in patients with breast cancer was related to OS, therefore, they recommned individualized vitamin D intake to assess breast cancer prognosis [ 238 ]. In case of lung cancer, Huang et al conducted a meta-analysis of eight cohort studies to evaluate the correlation between serum 25(OH)D level and OS.…”
Section: What Do We Know So Far About Vitamin D In Cancer Prevention and Prognosis From Clinical Trials?mentioning
confidence: 99%
“…The relationship between Vitamin D and breast cancer remains controversial. A recent meta-analysis demonstrated that while there is no relationship between nuclear VDR (NR1I1) expression and overall survival in patients with breast cancer, high total nuclear and cytoplasmic VDR expression was associated with improved survival outcomes [ 167 ]. Both the VDR and vitamin D 1-hydroxylase, the enzyme that generates the active Vitamin D3 ligand 1,25-dihydroxycholecalciferol, are expressed in the human breast.…”
Section: Other Nuclear Receptorsmentioning
confidence: 99%
“…Additionally, VDR expression correlates with the expression of ER. Interest has been provoked by growing evidence suggesting that adequate Vitamin D levels and intake inversely correlate with breast cancer risk [168][169][170], and that low levels of vitamin D are associated with an increased risk of recurrence or death in breast cancer patients [167,171]. This is arguably enough evidence to suggest that early breast cancer patients should at least supplement vitamin D if found to be deficient.…”
Section: Other Nuclear Receptorsmentioning
confidence: 99%
“…However, one conclusion that can be made is that the majority of breast cancers express VDR protein at a moderate level, and a significant percentage show high VDR immunoreactivity. A recent meta-analysis of the published immunohistochemical data has supported the concept that higher VDR protein is beneficial for patient survival, (62) but this likely depends on disease stage/grade and subtype.…”
Section: Vdr Expression In Relation To Clinical Parametersmentioning
confidence: 99%